KERAJAAN MELAYU KUNO: Tinjauan Sejarah Jambi Hingga abad 13 - Arif Rahim (Jurnal Ilmiah Dikdaya, 2022)
This paper focuses on several issues surrounding the existence of the Malay Kingdom which to this day still hold many unanswered issues, especially regarding the origins of the kingdom, the ruling kings, the central government, and the scope of the region. This research work is expected to contribute to the development of knowledge, especially about the local history of Jambi, and can be used as consideration by related institutions to preserve historical and cultural values and for the development of the tourism industry in the Jambi region. By using a multidimensional approach and supported by the application of historical methods that refer to scientific historical research procedures, it is hoped that the questions raised in the formulation of the problem will be expressed objectively and systematically. The results show that the Malay kingdom has its roots in three ancient pre-Malay kingdoms, namely Koying, Tupo, and Kantoli, which grew in the 4th century to the 7th century AD. The Malay kingdom emerged as an independent state marked by sending envoys to China. at 644-645M. The center of the kingdom at that time was in Jambi. Since 685 the Malay Kingdom was under Srivijaya control but the Malay port still functioned as an important port. The Malay kingdom re-emerged as an independent kingdom in the 12th century after the Srivijaya kingdom declined due to the Cola kingdom's attack. In this period the center of the kingdom had moved to Dharmasraya in the present-day area of West Sumatra. However, after the 1286 AD Pamalayu expedition, the Malay Kingdom was forced to vazal kingdom status by recognizing the power of Singhasari and Majapahit. Entering the 14th century under Adityawarman, the Malay Kingdom grew into the largest kingdom in Sumatra but the center of the kingdom moved to Pagaruyung, an area located in the natural center of Minangkabau, West Sumatra Province today.